Sustaining and Impeding Factors of Microfinance Services for Micro-enterprises Development - Ph. Romen Sharma , Rashmi Singh , Shantanu Kumar Dubey and Shridhar Patil, (Indian Journal of Extension Education, 2013)
The present study examines the sustaining and impeding factors of the microfinance services as perceived by thebeneficiaries and dropout clients, and it also investigates the reason for not availing the microfinance services by the nonbeneficiaries. Study included 40 microfinance beneficiaries, 30 microfinance drop-outs and 30 non-beneficiariesconstituting the total sample of 100 respondents. Responses of the subjects were collected through an open endedquestionnaire. Garrett's ranking was used to rank order the factors. The study revealed that ease of access and relatedservices of micro-credit at village level and lower capital interest rate were the sustaining factors whereas insensitivity ofmicrofinance institution (MFI) to type of enterprises, business cycle, clients' socio-economic and -personalcircumstances; the norm of weekly repayments and savings pressure were the impeding factors. Fear of losing theirproperty at default repayment and perceived weekly repayments pressure were the reasons for not availing themicrofinance services.